Some more inverse solutions for steady flows of a second-grade fluid - Siddiqui, A.M.; Mohyuddin, M.R.; Hayat, T.; Asghar, S. (Archives of Mechanics, 2003)
Inverse solutions of the equations of motion of an incompressible second-grade fluid are obtained by assuming certain forms of the stream function. Expressions for streamlines, velocity components and pressure distributions are given in each case and compared with the known results.